Thinking Processes in Numeracy: Influencing Factors, Content, and Varieties of Thinking Processes - Munzayanah, Nurul; Usodo, Budi; Fitriana, Laila; Nurhasanah, Farida (Universitas Wiralodra, 2025)
Numeracy is an important skill that enables students to understand mathematical concepts and solve problems in real-life contexts. According to the Programme for International Student Assessment (PISA), numeracy refers to the ability to use, interpret, and communicate mathematical information in everyday contexts. However, the 2022 PISA results show that Indonesia's average score in numeracy has declined compared to 2018 (OECD, 2023). This indicates that many students still struggle with the stages of thinking processes needed to solve mathematical problems correctly. This study aims to systematically examine the various factors that influence, content, and variations in students' thinking processes in numeracy. This research uses the PRISMA 2020 method by analysing 22 articles selected from the range of 2020-2024. The results showed that the most studied variations included mathematical thinking processes, mathematical literacy thinking processes, and thinking processes in solving problems. Algebra is the most researched content, because it has a framework that includes detailed stages in the thinking process, such as information identification, symbolic representation, and concept application. The most reviewed factors in the thinking process are mathematical ability and cognitive style. Students with high mathematical ability are more systematic in thinking, while students with medium and low ability tend to need scaffolding. Students with field independent cognitive style showed higher creativity than field dependent students.